Valorization of an 'Enemy Language': Politics of 'Progressive Anti-War' Position and English-Worship in the Japanese TV Show Massan. Issue 2 (3rd May 2020) - Doerr, Neriko Musha
ABSTRACT: This article analyzes portrayals of English in Japan during World War II in Massan, a Japanese television show that features the life of a mixed-race bilingual couple, Masaharu (the Japanese husband) and Ellie (the Scottish wife), and their adopted Japanese daughter (Ema) living in Japan. I argue that the show constructs a hierarchy of languages where English is valorized as a sign of an anti-war position, speaking one's mind and material wealth, all framed as progressive, in contrast to Japanese language. As the use of language is connected to race relations in the drama, this hierarchisation of English and Japanese languages is consistent with the historical and current valorization of English and whiteness in Japan. However, this hierarchy contradicts the show's explicit message of inclusiveness of all races. This article analyses a set of performative messages conveyed by this highly popular drama in the current Japanese political and racial context to show the ways uses of language convey unarticulated and sometimes contradictory messages.